FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA LAHAN DI KAWASAN WISATA SEMBALUN - FADILA IZZATUN HASNA; IWAN HARSONO; ENDANG ASTUTI (GANEC SWARA, 2024)
This research aims to determine the factors that influence land prices in the Sembalun tourist area. The types of data used are secondary data and primary data. The number of samples used in this research was 40. The data collection techniques used were interviews, and distributing questionnaires containing questions about land price, land area, distance to socio-economic centers, and distance to main roads. The analysis tool used is Multiple Linear Regression Analysis using the SPSS 23 for Windows program. The research results show that partially the Land Area variable on land prices has a positive and insignificant effect on land prices, while the Distance to Socio-Economic Center variable has a negative and significant effect on land prices, the Distance to Main Road variable has a negative and significant effect on land prices and simultaneously The variables Land Area, Distance to the Socio-Economic Center and Distance to the Main Road have a significant effect on Land Prices in the Sembalun Tourism Area.